Phylogenetics and Gene Structure Dynamics of Polygalacturonase Genes in Aspergillus and Neurospora crassa - Jin-Sung Hong; Ki-Hyun Ryu; Soon-Jae Kwon; Jin-Won Kim; Kwang-Soo Kim; Kyong-Cheul Park (The Plant Pathology Journal, 2013)
Polygalacturonase (PG) gene is a typical gene family present in eukaryotes. Forty-nine PGs were mined from the genomes of Neurospora crassa and five Aspergillus species. The PGs were classified into 3 clades such as clade 1 for rhamno-PGs, clade 2 for exo-PGs and clade 3 for exo- and endo-PGs, which were further grouped into 13 sub-clades based on the polypeptide sequence similarity. In gene structure analysis, a total of 124 introns were present in 44 genes and five genes lacked introns to give an average of 2.5 introns per gene. Intron phase distribution was 64.5% for phase 0, 21.8% for phase 1, and 13.7% for phase 2, respectively. The introns varied in their sequences and their lengths ranged from 20 bp to 424 bp with an average of 65.9 bp, which is approximately half the size of introns in other fungal genes. There were 29 homologous intron blocks and 26 of those were sub-clade specific. Intron losses were counted in 18 introns in which no obvious phase preference for intron loss was observed. Eighteen introns were placed at novel positions, which is considerably higher than those of plant PGs. In an evolutionary sense both intron loss and gain must have taken place for shaping the current PGs in these fungi. Together with the small intron size, low conservation of homologous intron blocks and higher number of novel introns, PGs of fungal species seem to have recently undergone highly dynamic evolution.